Analisa Faktor yang Mempengaruhi Kegagalan PadaProses Produksi Finned Tube Menggunakan Mesin Spiral Finned Tube di PT. Arezda Purnama Loka - Alfin Daffa Mubarok; Kardiman Kardiman; Iwan Nugraha Gusniar (Peneliti.net, 2022)
PT. Arezda Purnama Loka was founded in 1983, Arezda is one of the companies engaged in manufacturing. In the production process, sometimes there are often failures, therefore the purpose of this study is to find out the factors that affect the production process of the finned tube production process using a pt finned tube spiral machine. Arezda Purnama Loka. This research uses qualitative research, data collection is carried out using observation methods, interviews, and literature studies, while data processing uses fishbone analysis. From the results of the study, it was found that the type of failure of the production process in the spiral finned tube machine was caused by several factors such as man, material, methode, machine.